Verso la tecnologia 6G per i luoghi della cultura: Trasmissione di enormi quantità di dati e informazioni in pochi secondi - Papi, Luca; Russo, Francesco Paolo (Archeomatica, 2023)
Considering the remarkable historical, artistic, monumental, demoethno-anthropological, archaeological, archival and national library heritage, in order to improve the management and safety of places of culture, it becomes essential to focus attention on the new 6G technology which will allow the fusion of digital world with the physical world capable of transmitting huge amounts of data and information in seconds. The places of culture (archaeological areas, archaeological parks, museums, monuments, archives, libraries), like other built places, thanks to 6G technology and its flexibility, versatility, sustainability, reliability, will be able to become completely interconnected.